Neural Differentiation and Incorporation of Bone Marrow-Derived Multipotent Adult Progenitor Cells after Single Cell Transplantation into Blastocyst Stage Mouse Embryos - C. Dirk Keene; Xilma R. Ortiz‐González; Yuehua Jiang; David A. Largaespada; Catherine M. Verfaillie; Walter C. Low (2003)
Previously we reported the characterization of multipotent adult progenitor cells (MAPCs) isolated from the bone marrow of rodents. In that study, single murine MAPCs derived from ROSA-26, β-galactosidase (β-Gal)-positive transgenic mice were injected into E3.5 C57/Bl6 mouse blastocysts. The resultant chimeric blastocysts were then implanted into pseudopregnant females and were allowed to develop naturally through birth and into adulthood. Chimeric mice were sacrificed 6 to 20 weeks after birth, and were processed for histological analysis. β-Galactosidase activity was identified in all organs and tissues examined, and tissuespecific differentiation and engraftment was confirmed by colabeling with antibodies that recognize β-Gal and tissue-specific markers. In the present study we have examined neural engraftment derived from the clonal expansion of a single MAPC during rodent development, and characterized the neural phenotype of MAPCs in the resultant chimeric animals. Donor cell-derived β-Gal activity was evident throughout the brain. Double and triple immunofluorescent labeling studies revealed MAPC-derived neurons (NeuN/β-Gal) and astrocytes (GFAP/β-Gal) in the cortex, striatum, medial septal nucleus, hippocampus, cerebellum, substantia nigra, and thalamus. More specifically, donor-derived neurons contributed to each of the cellular layers of the cortex; the pyramidal and granule cell layers, as well as the hilus, of the hippocampus; Purkinje and granule cell layers in the cerebellum; and GABAergic cells in the caudate and putamen. This study haracterizes the potential for MAPCs to differentiate into specific neuronal and glial phenotypes, and to integrate normally during development, after implantation into blastocysts, and provides additional evidence that MAPCs exhibit properties similar to embryonic stem cells.